Development and Validation of a Nomogram for Predicting Tigecycline-Related Coagulopathy: A Retrospective Cohort Study - Li Z; Zeng Q; Xu S; Li Y; Tang T; Shi J; Song X; He W; Chen L; Liu G; Gao B; Zheng J; et al. (Infection and Drug Resistance, 2023)
Zhaolin Li,1,* Qiaojun Zeng,1,* Shuwan Xu,2,* Yuewei Li,1 Tiantian Tang,1 Jianting Shi,1 Xueming Song,1 Wenman He,1 Liang Chen,1 Guirong Liu,1 Boying Gao,3 Jianming Zheng,4 Linjie Huang,1 Ming Chen,1 Shanping Jiang1 1Department of Pulmonary and Critical Care Medicine, Sun Yat-sen Memorial Hospital, Sun Yat-sen University, Guangzhou, People’s Republic of China; 2Department of Cardiology, the Eighth Affiliated Hospital, Sun Yat-sen University, Shenzhen, People’s Republic of China; 3Breast Tumor Center, Sun Yat-sen Memorial Hospital, Sun Yat-sen University, Guangzhou, People’s Republic of China; 4Cardiovascular Medicine Department, Sun Yat-sen Memorial Hospital, Sun Yat-sen University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shanping Jiang; Ming Chen, Department of Pulmonary and Critical Care Medicine, Sun Yat-sen Memorial Hospital, Sun Yat-sen University, Yan-jiang Xi Road 107, Guangzhou, 510120, People’s Republic of China, Tel +86-20-81332441, Email jiangshp@mail.sysu.edu.cn; chenm69@mail.sysu.edu.cnBackground: Although tigecycline is an effective drug against drug-resistant bacteria, it demonstrated a higher all-cause mortality than comparator antibiotics and a high incidence of coagulation disorders which can be accompanied by severe bleeding. At present, a predictive model for tigecycline-related coagulopathy is not readily available, and the prognostic value of coagulopathy in tigecycline-administered patients has not been elucidated. In this paper, we investigate the association between tigecycline-related coagulopathy and in-hospital mortality to develop a nomogram for the prediction of tigecycline-related coagulopathy.Methods: This retrospective cohort study includes 311 adults prescribed with tigecycline from 2018 to 2020. The primary cohort and validation cohort were constructed by dividing the participants in a ratio of 7:3. The endpoint is tigecycline-related coagulopathy, defined as a condition with no abnormality in coagulation prior to tigecycline application but developed the following symptoms upon prescription: activated partial thromboplastin time (APTT) extended by > 10 s than the upper limit of normal (ULN), prothrombin time (PT) prolonged for > 3 s than the ULN or reduced serum level of fibrinogen to < 2.0 g/L. A predictive nomogram based on logistic regression was subsequently constructed.Results: Tigecycline intake for over 7 days, combined other antibiotics, initial PT, initial fibrinogen and estimated glomerular filtration rate (eGFR), are independent prognostic factors of tigecycline-related coagulopathy. The primary and validation cohort each has an area under the receiver operating characteristic curve (AUC) of 0.792 (0.732– 0.851) and 0.730 (0.629– 0.832) for nomogram, respectively. Furthermore, the fitted calibration curve illustrated adequate fit of the model, while the decision curve analysis demonstrated good clinical value. Survival curves showed a high mortality rate among patients with tigecycline-related coagulopathy.Conclusion: This nomogram exhibited helpful clinical value in predicting tigecycline-related coagulopathy that could reduce the high mortality rate of patients prescribed with tigecycline.Keywords: tigecycline, drug-resistant bacteria, coagulopathy, nomogram